Muslim Students' Dispositional Mindfulness and Mental Well-Being: The Mediating Role of Core Self-Evaluation - Mohammad Saleem; Touseef Rizvi; Irfan Bashir (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2022)
This study analyses the mediating role of Core Self-evaluation (CSE) on the relationship between dispositional mindfulness and mental wellbeing. A sample of 184 Muslim students (Mage = 22.08) studying in the different universities completed the self-report measures of the Mindful Attention Awareness Scale (MAAS), the Core Self-evaluations Scale (CSES), and the Warwick–Edinburgh Mental Well-being Scale (SWEMWBS). The collected responses are subjected to multiple regression and mediation analyses. The results revealed that dispositional mindfulness and core self-evaluations significantly predicted mental well-being. It is found that core self-evaluation fully mediates the effect of dispositional mindfulness on mental well-being. Moreover, it is also observed that measures of dispositional mindfulness, core self-evaluation, and mental well-being are indifferent with respect to students’ gender. Therefore, the study highlights the importance of core self-evaluation and explains a possible process by which depositional mindfulness enhances Muslim students' mental well-being.